Role of Non-Hepatotropic Viruses in Acute Sporadic Viral Hepatitis and Acute-on-Chronic Liver Failure in Adults - Moeen Ul Huq, Rizwan Ur Rehman, M. Nabeel Mohsin, Fahad Usman, Paula Jativa, Maria Jose Heredia (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Viral infections, drugs, metabolic disorders, and autoimmune processes can cause hepatitis, which is a diffuse inflammatory condition of the liver. Hepatitis E (HEV) and hepatitis A (HAV) viruses are the most common causes of acute viral hepatitis (AVH). AVH and chronic liver failure (ACLF) patients were studied to determine whether they were infected with various hepatotropic and non-hepatotropic viruses. Patients and Methods: This prospective study was conducted on 186 adult patients with ACLF and AVH in the Department of Gastroenterology, DHQ Teaching Hospital and Mufti Mahmood Memorial Hospital, Dera Ismail Khan from September 2020 to August 2022. Our study included consecutive patients with acute viral hepatitis who had a definite viral etiology, a fever or jaundice that developed after 3 weeks, and an ALT that was 2x the upper limit of normal. There were three serological tests performed for all the patients: hepatitis (A, B, C, D, and E), Epstein-Barr virus (EBV), and non-hepatitis (CMV). Data analysis was carried out in SPSS version 26. Results: Of the total 186 samples investigated, the incidence of ACLF and AVH was 60 (32.3%) and 126 (67.7%) respectively. The prevalence of confirmed etiology such as HEV, HAV, HBV, and HCV was 98 (52.7%), 29 (15.6%), 20 (10.8%), and 2 (1.1%) respectively. The mixed viral etiology and Epstein-Barr virus was present in 18 (9.7%) and 19 (10.2%) respectively. The most prevalent cause of infection was HEV found in 76 (60.3%) AVH and 42 (70%) ACLF cases. The mortality rate among AVH patients was significantly lower 2.4% (n=3) than ACLF 23.3% (n=14). As compared to ACLF patients, AVH patients had significantly higher infections caused by non-hepatotropic viruses (24 vs. 3, p=0.001). There were significantly more mixed infections in AVH as opposed to ACLF (28 vs. 4, p<0.001). Conclusion: The present study concluded that both AVH and ACLF patients were susceptible to HEV-associated hepatitis. There were significant numbers of patients with AVH being infected with non-hepatotropic viruses including CMV and EBV. These viruses are much less common in patients with ACLF. Keywords: Epidemiology, Non-hepatotropic virus, Acute viral hepatitis, Acute chronic liver failure